Understanding how a culture of wellness was established and is perceived at a large Texas public school district that has an award-winning employee wellness program - Rodriguez-Sarabia, Cordelia (My University, 2025)
The COVID-19 global pandemic not only transformed but also reinvented the U.S. workforce, with many workers returning to the workplace demanding more work–life balance options for increased quality of life and health. As a result, many employers explored employee health promotion programs, also known as employee wellness programs (EWPs). Wellness programs in the academic setting, however, are typically designed and implemented for students, not faculty and staff. Historically corporations have been the leaders in instituting EWPs (Amaya et al., 2019). Wellness programming is consistent with the college mission, making it ideal to offer programs to their employees (Linnan et al., 2010). An obstacle for academic institutions, like colleges, is that they have unique challenges due to their large and diverse employee population, including maintenance staff, administrators, and faculty from different disciplines (Hill-Mey et al., 2015). In addition, few specific examples how to establish a successful EWP and a culture of wellness on community college campuses are available. In fact, the limited amount of community college EWPs that have received recognition for creating a culture of wellness was the reason for a change in the study site. The purpose of this study was to understand how a culture of wellness was established and perceived at the United Independent School District, a large Texas public school that has received recognition for their EWP from the American Heart Association for several years. Understanding key elements of their EWP can provide value to other academic institutions, like community colleges, that are trying to establish a culture of wellness at their campus and may contribute to policy or practice for such initiatives.
Keywords: Culture of wellness; Worksite wellness; Leadership; Perception; Employee wellness program; Learning culture